Megastigmane glycosides from Streblus ilicifolius (S.Vidal) Corner and their anti-inflammatory activity. (April 2023) - Huang, Yan; Pan, Liwei; Chang, Yanling; Liang, Xiaoqin; Hou, Ping; Ren, Chenyang; Xu, Weifeng; Yang, Ruiyun; Li, Jun; Liu, Buming
Abstract: Twelve undescribed megastigmane glycosides, streilicifolosides A−L (1 –12 ), together with 8 known analogues (13 –21 ) were isolated from the leaves of Streblus ilicifolius (S.Vidal) Corner. Their plannar structures were elucidated using extensive NMR spectroscopic methods (1D and 2D-NMR spectroscopy), and HRESIMS spectroscopic data analyses. The absolute configurations of the undescribed compounds were determined by the glucose-induced shift-trend, calculated and experimental circular dichroism spectroscopy. All the compounds were tested for inhibitory effects on the production of NO in LPS-treated RAW264.7 cells, and streilicifoloside E and platanionoside D exhibited potent anti-inflammatory activity comparable to that of the positive control, with IC50 values of 26.33 and 21.84 μM, respectively. Furthermore, these two compounds markedly decreased the secretion of PGE2 and TNF-α and inhibited the expression of COX‒2, iNOS and NF-κB/p65 in LPS-induced RAW264.7 cells in a dose-dependent manner. In addition, the structure−activity relationships of the isolates were also discussed. The results suggest that streilicifoloside E and platanionoside D could be used as potential candidates for the development of new anti-inflammatory agents. Graphical abstract: Twelve previously undescribed megastigmane glycosides were isolated from Streblus ilicifolius (S.Vidal) Corner. Some of them exhibited potent anti-inflammatory activities. Image 1 Highlights: Twenty-one megastigmane glycosides were isolated from Streblus ilicifolius. Of these, twelve previously undescribed compounds were discovered. Some isolates exhibited potent anti-inflammatory effects.